LATIN AMERICAN CREATOR (SUB)CULTURES ON TIKTOK: VISIBILITY, RESISTANCE, AND CONTEXTUAL RESEARCH - Jaramillo-Dent, Daniela; Divon, Tom; da Rosa Amaral, Adriana; Tabasnik, Rafaela; Craig, David; Arriagada, Arturo; Cifuentes, Matias; Lopez del Pozo, Melanie; Valiati, Vanessa; Ferrareli, Camila; Perevedentseva, Maria (AoIR Selected Papers of Internet Research, 2026)
Latin America features diverse cultures, landscapes, life experiences, and ethnicities, shaped by socioeconomic inequalities and ongoing political turbulence. These structural disparities extend to the digital sphere, shaping the opportunities and challenges faced by content creators in the region. The promise of fame, financial success, and global visibility celebrated in Western content creation is often unfulfilled in other regions. Instead, Latin American creators must navigate layers of discrimination and (in)visibility, stemming from linguistic, geographic, and identity-based vulnerabilities, while also contending with algorithmic systems that privilege certain types of content.Despite the global expansion of influencer and creator industries, research on creators outside the West remains scarce (Abidin & Brown, 2019; Poell et al., 2024). This panel seeks to address this gap by focusing on Latin America’s diverse creator landscape and platform dynamics. Given its high penetration in the region, TikTok provides an ideal lens to examine these challenges. By 2025, TikTok is projected to reach 173 million users in Latin America (Bianchi, 2022), making it a dominant force in the region’s digital ecosystem. Unlike earlier platforms, TikTok’s algorithm-driven discovery system (Abidin, 2021) enables creators to reach new audiences beyond their immediate networks. Additionally, short vertical videos have become central to entertainment, music industries (Anonymized), and news consumption (Mulier et al., 2021; Newman et al., 2024). This has led to the broader “TikTokification” of social media where competing platforms such as Instagram Reels and YouTube Shorts have adopted similar algorithmic structures, interfaces, and affordances to mimic TikTok’s engagement-driven model (Agile Brand Guide, 2024).This panel draws from the findings of the Latin American Cultures on TikTok report (Anonymized), examining the evolving landscape of content creation in the region. Panelists will explore the shifting landscape for Latin American creators, addressing (1) the opportunities and challenges they face in the digital economy, (2) the monetization and visibility barriers shaping their sustainability, and (3) the complex interplay between their politics, subcultures, and the region’s rapidly expanding influencer industry. Bringing together scholars specializing in creator economies, platform governance, and digital cultures, each paper features researchers from across Latin America with deep-rooted experience in the region’s social, economic, and cultural contexts —from MA students and PhD candidates to assistant and associate professors.Setting the foundation for the panel’s broader discussion, the first paper presents a research agenda for studying Latin American creators on TikTok, focusing on governance, (de)monetization, and visibility divides. It examines how platform regulations, economic barriers, and algorithmic inequalities shape the region’s creator economy, revealing how TikTok privileges certain content and geographies while marginalizing others. By mapping the structural constraints that Latin American creators face, this paper establishes a critical framework for understanding the tensions between platform governance and local creative industries.Shifting towards local creator cultures, the second paper examines the so-called "Chilenazo" phenomenon —the return of Chilean creators to their homeland, navigating exclusion from global creator culture, after struggling to compete in the Mexican creator industry. It explores how platform nationalism (competition between U.S. and Chinese platforms), and cultural imaginaries shape creators’ professional aspirations, mobilities, and their perception of Chile as a site of creative and economic limitation.Continuing the theme of resistance, the third paper explores the contested identities of Latin American creators in Peru, analyzing how Peruvian activists repurposed TikTok’s affordances during the 2022-2023 political crisis. Drawing on the framework of everyday politics, it examines how creators strategically leveraged TikTok’s affordances to circumvent censorship, counter state narratives, and document human rights violations. This paper illustrates how TikTok, designed for entertainment, was transformed into a grassroots political tool, where digital creativity became an instrument of local defiance.The fourth paper shifts focus to activism and community-building, exploring the Brazilian TikTok subculture of prisoners’ wives (#MulherDePreso). It examines how women in relationships with incarcerated men in Brazil use TikTok to construct digital support networks, share survival strategies, and navigate the bureaucratic complexities of incarceration. Through hashtag activism and digital storytelling, this subculture reclaims visibility for an often-overlooked demographic, demonstrating how TikTok facilitates alternative forms of advocacy and solidarity beyond traditional activist spaces.The fifth analyzes how young Brazilian TikTokers remix, adapt, and localize global music hits on the platform. It explores how platform aesthetics and algorithmic virality fuel new forms of digital nostalgia, and cultural remixing subcultures, transcending time and location through dance trends. Rather than simply reviving old songs, these adaptations reflect a distinctly Brazilian approach to musical reinterpretation, illustrating how local creative cultures interact with and reshape globalized digital content.Together, these papers examine how Latin American creators engage with TikTok —as entrepreneurs, activists, or subcultural participants. By highlighting the region’s dynamic creator ecosystem, we aim to provide a nuanced understanding of how local cultures both influence and are influenced by global platforms, shaping visibility, agency, and creative expression while reflecting the richness and diversity of Latin American experiences.